079 Defective regeneration of oxidatively-inactivated 2-cys peroxiredoxins in SOD1-related Amyotrophic Lateral Sclerosis. Issue 3 (9th February 2012) - Rajan, S; Shaw, P; Wood-Allum, C
Abstract : Background: Peroxiredoxins (prxs) are abundant redox-sensitive anti-oxidant enzymes that reduce hydrogen peroxide (H2 O2 ) to water, becoming oxidised themselves in the process. Oxidised 2-cys prxs may either be returned to their reduced state by thioredoxin or become overoxidised. Overoxidised 2-cys prxs (PrxSO2/3 ) lose their hydroperoxidase activity but may then form multimers with a molecular chaperone function. Overoxidation of 2-cys prxs may be reversed by sulphiredoxin-1. Previous studies demonstrated altered levels of prxs in SOD1-ALS. This and prx anti-oxidant and protein chaperone roles relevant to existing pathogenetic hypotheses led us to ask whether the oxidation state of the 2-cys prxs might be altered in Amyotrophic Lateral Sclerosis (ALS). Hypothesis: We hypothesised that 2-cys prxs might spend longer in a more oxidised state in ALS and that this might have implications for disease pathogenesis. We aimed to test this hypothesis in models of SOD1 ALS in the first instance. Methods: Fibroblasts were obtained from patients with I113T SOD1-related familial ALS and age and sex-matched controls. Western blotting for total 2-cys prxs, PrxSO2/3, sulphiredoxin-1 and activated AP-1 (a transcriptional activator of sulphiredoxin-1) was performed on cells grown under basal conditions and after exposure to 300 mM H2 O2 for 15 min. Stress recovery experiments (15 min 300 mM H2 O2, washout, 26 h recovery) were performed with and without cycloheximide. Whole brain and spinal cord homogenates from G93A-overexpressing transgenic mice were also examined for PrxSO2/3 . Results: No difference in total 2-cys prxs was found between patient and control fibroblasts and minimal PrxSO2/3 was detected in either under basal conditions. Exposure to 300 mM H2 O2 for 15 min overoxidised 2-cys prxs to saturation with no detectable difference between patient and control cells. PrxSO2/3 recovery was, however, significantly delayed in patient fibroblasts. Sulfiredoxin-1 induction after H2 O2 -treatment was both delayed and reduced in patient fibroblasts compared to controls while levels of activated AP-1, a transcriptional regulator of sulphiredoxin 1, also increased less in patient fibroblasts after oxidative challenge. Both sulphiredoxin-1 induction and PrxSO2/3 recovery were abolished by cycloheximide pre-treatment. PrxSO2/3 was almost undetectable by western blotting in whole cord or brain preparations from G93A and non-transgenic littermate mice. Discussion: Delayed PrxSO2/3 recovery in I113T-FALS fibroblasts suggests that in this ALS model 2-cys prxs do spend longer in an oxidatively-inactivated state after oxidative challenge. Defence against H2 O2 will be impaired for longer after each such challenge raising the possibility of an above-normal rate of accumulation of oxidative damage with repeated exposures. The delay in PrxSO2/3 regeneration may be due to impaired AP-1 and in turn impaired sulphiredoxin-1 induction after oxidative stress, an induction dependent upon protein translation. How important the functional consequences of the deficit we have identified are remains to be seen. Work to reiterate our experiments in fibroblasts from non-SOD1 familial ALS, sporadic ALS and in motor neuronal cell models of ALS is underway.